Solution of the Structural Optimization Problem of a Multiagent Approach Based Cutter Design - Anosov, V.L.; Bohdanova, L.M.; Kolodyazhnyi, V.M.; Litovka, V.D. (Проблеми машинобудування, 2019)
This article proposes a decision support system project to find the optimal milling cutter design. At the preliminary design stage, morphological analysis is used. It allows us to find and systematize all possible milling cutter structures with the necessary functional purpose. To automate the design formation process, an algorithm based on a resolution method is applied, with the algorithm using the logic of first-order predicates. An enumeration of possible states and assembly of a milling cutter structure from ready-made elements are carried out.